Study on the Effect of High-Temperature Oxidation on the Phases of NiCrAlY-Cr Coatings with Different Thicknesses - CHEN Jiao, CHAI Yan, WANG Jianfeng, ZHANG Yao, CAO Zheng, FANG Ziwen, ZHANG Zhaolu, WANG Yuanyuan, HE Ni (Cailiao Baohu)
In order to clarify the influence mechanism of Cr diffusion barrier layer on the oxidation performance of NiCrAlY coating under high temperature conditions， NiCrAlY coatings and NiCrAlY-Cr composite coatings with Cr barrier layers of different design thicknesses (50， 100，150 μm) were prepared using plasma spraying technology.The phase composition changes of the coatings were analyzed using X-ray diffraction(XRD)， while the microstructure of the coatings was examined using scanning electron microscopy (SEM).The element distribution in the coatings and oxidation layers was analyzed by energy dispersive spectrometer (EDS) attached to the SEM.The high-temperature oxidation behavior of NiCrAlY-Cr coatings with different thicknesses of Cr barrier layers was investigated.Results showed that both the deposited NiCrAlY and NiCrAlY-Cr coatings were mainly composed of Ni3Al.After oxidation at 850 °C for 30 h， both NiCrAlY and NiCrAlY-Cr coatings formed α-Al2O3 and Cr2O3 on their surfaces.When the oxidation temperature was increased to 950 °C， after 30 h of oxidation， all three NiCrAlY-Cr composite coatings with different Cr barrier layer thicknesses showed a dominant Ni3Al phase on their surfaces， along with the formation of α-Al2O3， Cr2O3， and characteristic diffraction peaks of NiCr2O4.After 65 h of oxidation at 850 °C， the main phases in NiCrAlY and NiCrAlYCr composite coatings with different thicknesses of Cr barrier layers were α-Al2O3， Cr2O3， NiCr2O4 and Ni3Al.With the extension of oxidation time to 100 h， the phases in the NiCrAlY coatings and NiCrAlY-Cr composite coatings with Cr barrier layers of different design thicknesses remained dominated by α-Al2O3， Cr2O3， NiCr2O4 and Ni3Al after oxidation at both 850 °C and 950 °C.The dense protective layer formed by α-Al2O3， Cr2O3 and NiCr2O4 on the surface of NiCrAlY-Cr coatings in high-temperature environments provided significantly better high-temperature oxidation resistance compared to NiCrAlY coatings.